2018
DOI: 10.21640/ns.v10i20.1392
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity and phenolic content of propolis extracts obtained by different extraction methods

Abstract: Introduction: The data available regarding the chemical composition and procedures for the extraction of the propolis are currently inconclusive. In this study the chemical groups present in the extracts of a propolis mixture obtained by different methods were identified. Additionally, their content of polyphenols and flavonoids was determined, and antioxidant and antibacterial activity was studied.                       Method: The extracts were obtained by maceration and for the ultrasonic and microw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In other studies, the authors reported that UAE was superior to 2-day shaking extraction in terms of the extraction of flavonoids but inferior to the latter in terms of the extraction of phenolic compounds. Despite different content of bioactive compounds in the propolis extracts, no significant impact of these differences on antimicrobial properties was observed as all extracts inhibited the bacterial growth with similar strengths (Luján et al 2018). Likewise, in the studies by Yeo et al (2015), an extract with a considerably higher content of bioactive compounds obtained in an ultrasound-assisted procedure presented with a growth inhibition effect being only slightly higher for Staphylococcus epidermidis and Bacillus subtilis and lower for E. coli as compared to an extract obtained in a traditional, 1-day maceration process.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, the authors reported that UAE was superior to 2-day shaking extraction in terms of the extraction of flavonoids but inferior to the latter in terms of the extraction of phenolic compounds. Despite different content of bioactive compounds in the propolis extracts, no significant impact of these differences on antimicrobial properties was observed as all extracts inhibited the bacterial growth with similar strengths (Luján et al 2018). Likewise, in the studies by Yeo et al (2015), an extract with a considerably higher content of bioactive compounds obtained in an ultrasound-assisted procedure presented with a growth inhibition effect being only slightly higher for Staphylococcus epidermidis and Bacillus subtilis and lower for E. coli as compared to an extract obtained in a traditional, 1-day maceration process.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of total polyphenols was 20.60%, and the concentration of total polyphenols expressed in GAE was 20,595.37 mg GAE/100 g. This result agrees with that obtained by Zhang et al (2016) [ 35 ] who found 19,280 mg GAE/100 g of phenolic compounds in ethanol extract of Chinese propolis (EECP), 21,770 mg GAE/100 g in ethanol extract of Eucalyptus propolis (EEEP), and 13,507 mgGAE/100 g in ethanol extract of Baccharis propolis (EEBGP) [ 35 ]. The content of phenolic compounds in propolis is highly variable because it depends on the diversity of plant species to which bees have access during its preparation [ 36 ]. On the other hand, according to Bakchiche, (2017) [ 37 ] each species of bee has a habit of collecting resin that increases the regional and interspecific variations in the composition of propolis.…”
Section: Resultsmentioning
confidence: 99%